Climate Security Observatory – GUATEMALA. Summary for policymakers - Liebig, Theresa Ines (2023)
Guatemala is considered to be one of the most exposed and vulnerable countries in Latin America to climate variability and extreme weather events, as well as non-climatic natural events. It is also a primary hotspot for climate change, as it is highly exposed to extreme weather events like tropical storms and droughts and has low capacity to cope with these impacts. This profile, derived from the Climate Security Observatory, answers: 1) HOW does climate worsen the root causes of conflict? 2) WHERE are the most vulnerable areas to climate induced insecurities and risks? 3) WHO are the vulnerable groups to climate and security risks that should be targeted? and 4) WHAT needs to be done to break the cycle between climate and conflict?